Arsenate minerals from Hungary - Szakáll Sándor; Birch W. D.; Postl W.; Kovács Árpád (University of Szeged, Department of Mineralogy, Geochemistry and Petrology Szeged, 1994)
In this paper we introduce some arsenate minerals found recently in the ore deposits and ore indications in Hungary. The essential demand of their formation was the presence of arsenopyrite or the members of the tetrahedrite group. Under such circumstances it was generally possible to identify arsenate minerals from the oxidized zone of the ore deposits. Arseniosiderie, segnitite, scorodite and probably arsenbrackebuschite were found in the hydrothermal polimetallic ore veins at Nagybörzsöny, Börzsöny Mts. Olivenite, mimetite, beudantite and a tyrolite-like arsenate mineral were found in the hydrothermal-metasomatic iron ore deposit with accessory at Rudabánya, Rudabánya Mts. In a limestone quarry near Pécs, Mecsek Mts. olivenite, conichalcite and tyrolite were found. Talmessite and picropharmacolite were identified in dolomite concretions in the sedimentary infiltrated uranium ore deposit at Kővágószőlős, Mecsek Mts. Scorodite and pharmacosiderite were observed in the epithermal alunite veins of the limnoquartzite at Mád, Tokaj Mts. Pharmacosiderite was identified in the epithermal mineral assemblage of hydroquartzite at Gyöngyössolymos, Mátra Mts.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok